Shape of snack foods does not predict snack intake in a sample of preschoolers: a cross-over study - Boyer Lauren E; Laurentz Sara; McCabe George P; Kranz Sibylle (BMC, 2012)
Abstract Background In the past decade, the proportion snacking has increased. Snack foods consumed are predominantly not nutritious foods. One potential venue to increase children's diet quality is to offer healthy snack foods and we explored if shaped snack foods would lead to increased consumption. Methods We investigated the consumption of high-fiber snacks (banana bread, pancakes, and sandwiches) served either in normal (round, square) or shaped (heart, hands, animals) form to preschoolers 2-5 years old attending a local child care center (n = 21). The 9 weeks long, prospective, cross-over intervention study was designed to expose each child repeatedly to each snack in each shape (4 times per snack). Snacks were served as morning or afternoon snack and caretakers' reports were used to account for the child's consumption of a meal preceding the study snack (breakfast or lunch). Results There was no significant difference in snack consumption between the shaped and normal snacks. However, the mean energy intake from snacks was significantly greater for Caucasian children compared with Asian children. Further, Asian children consumed much less banana bread than the other two snacks. Overall, children who had not eaten breakfast or lunch prior to the morning or afternoon snack ate significantly more calories from the snacks (84.1 kcal, p-value < 0.0001). Conclusion Findings of this study confirm previous research that the shape of the foods does not affect snack consumption in children. However, we also report two unexpected findings: a) the strong interaction between ethnicity and snack consumption and b) that Asian children consumed much less banana bread than Caucasian children. The role of children's ethnic background profoundly affects snack preference and must be considered in the study of children's eating behaviors and in interventions to promote healthy eating habits.